Pengaruh Produk Domestik Regional Bruto (PDRB) Inflasi dan Suku Bunga Terhadap Produk Deposito Berjangka Di Bank SULUTGO Tahun 2020-2022: (Studi pada Bank Sulutgo Tahun 2020-2022) - Fikranto Ahmad; Niswatin Niswatin; Usman Usman (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to determine the influence of gross regional domestic product (GRDP), inflation and interest rates on time deposit products at Sulutgo banks. The type of method used in this research is a quantitative method with data collection techniques using secondary data and library data. The number of samples in this research is 36 samples in 2020-2022. The tool used in this research uses multiple linear regression analysis. The results of this research show that gross regional domestic product (GRDP), inflation and interest rates have an influence on time deposit products. 4. Simultaneously gross regional domestic product (GRDP), inflation and interest rates have a very limited but very limited influence on the dependent variable with a determinant value of 15.6% while the remaining 84.4% is influenced by other variables not included in the regression model and The presence of Covid-19 caused the economy in Indonesia to decline greatly at that time.